Children’s Mental Health Visits to the Emergency Department: Factors Affecting Wait Times and Length of Stay - Amanda S. Newton; Sachin Rathee; Simran Grewal; Nadia Dow; Rhonda J. Rosychuk (Emergency Medicine International)
Objective. This study explores the association of patient and emergency department (ED) mental health visit characteristics with wait time and length of stay (LOS). Methods. We examined data from 580 ED mental health visits made to two urban EDs by children aged ≤18 years from April 1, 2004, to March 31, 2006. Logistic regressions identified characteristics associated with wait time and LOS using hazard ratios (HR) with 95% confidence intervals (CIs). Results. Sex (male: HR=1.48, 95% CI=1.20–1.84), ED type (pediatric ED: HR=5.91, 95% CI=4.16–8.39), and triage level (Canadian Triage and Acuity Scale (CTAS) 2: HR=3.62, 95% CI=2.24–5.85) were statistically significant predictors of wait time. ED type (pediatric ED: HR=1.71, 95% CI=1.18–2.46), triage level (CTAS 5: HR=2.00, 95% CI=1.15–3.48), number of consultations (HR=0.46, 95% CI=0.31–0.69), and number of laboratory investigations (HR=0.75, 95% CI=0.66–0.85) predicted LOS. Conclusions. Based on our results, quality improvement initiatives to reduce ED waits and LOS for pediatric mental health visits may consider monitoring triage processes and the availability, access, and/or time to receipt of specialty consultations.